Kontribusi Perempuan dalam Periwayatan Hadis: Perbandingan Riwayat Sahabat Laki-laki dan Perempuan dalam Empat Kitab Sunan - Fera Rahmatun Nazilah; M. Alvin Nur Choironi (Departement of Hadith Sciences, Faculty of Ushuluddin, UIN Syarif Hidayatullah, Jakarta, 2025)
This study analyzes hadiths concerning women in the four Sunan collections: Sunan Abū Dāwud, Sunan al-Tirmidhi, Sunan al-Nasā’i, and Sunan Ibn Mājjah. Employing a qualitative approach supported by descriptive quantitative analysis, the research collects data through keyword tracing and identification of female transmitters, followed by thematic categorization and analysis of transmitter distribution and narration characteristics. The findings reveal that hadiths about women cover a wide range of topics, including virtues, prohibitions, domestic roles, and social roles. Female transmitters, especially the wives of the Prophet Muhammad Peace be upon Him, provide narrations rich in personal and detailed perspectives, while male transmitters tend to report public and normative aspects. These differences demonstrate a complementary relationship that enriches our understanding of the Prophet’s life and the role of women in early Islamic society. The study emphasizes the importance of integrating narrations from both genders in hadith studies and highlights their relevance for strengthening the role of women in contemporary Islamic scholarship.